Microbial Response to Fungal Infection in a Fungus-Growing Termite, Odontotermes formosanus (Shiraki) - Wu, Chen-Yu; Meng, Jing; Merchant, Austin; Zhang, Yi-Xiang; Li, Mu-Wang; Zhou, Xu-Guo; Wang, Qian (Frontiers in Microbiology, 2021)
The crosstalk between gut microbiota and host innate immunity has been one of the research foci of microbiome, one of the most dynamic emerging fields. The purpose of this study was to determine how the intestinal microbes respond to fungal infection, using termites as a model system due to their reliance on gut symbionts for food intake as well as maintaining host health. Here, we used Metarhizium robertsii, an entomopathogenic fungus, to infect Odontotermes formosanus, a fungus-growing termite in the family Termitidae and documented the dynamic changes in the host gut microbiota in the due process via a combination of bacterial 16s rDNA sequencing, metagenomic shotgun sequencing, and transmission electron microscopy. Our analyses found significant changes in the abundances of specific phyla post-fungal infection alongside substantial changes in the functional categories of and interactions among phyla. The resultant compositional and functional changes in response to fungal infection in a higher termite advances our understanding of the role of gut microbiota in maintaining host homeostasis and immunostasis, as well as the consequences of gut dysbiosis in host susceptibility to infections.